Biodegradable 2D Fe–Al Hydroxide for Nanocatalytic Tumor‐Dynamic Therapy with Tumor Specificity. Issue 11 (9th October 2018) - Cao, Zhenbang; Zhang, Liang; Liang, Kang; Cheong, Soshan; Boyer, Cyrille; Gooding, J. Justin; Chen, Yu; Gu, Zi
Abstract: Therapeutic nanocatalysis has emerged as an intriguing strategy for efficient cancer‐specific therapy, but the traditional inorganic nanocatalysts suffer from low catalytic efficiency and difficulty in biodegradation, hindering their further clinical translation. Herein, a tumor microenvironment‐triggered, biodegradable and biocompatible nanocatalyst employing 2D hydroxide nanosheet is presented, and is shown to have high catalytic capacity to efficiently produce abundant hydroxyl radicals under the tumor microenvironment and consequently kill tumor cells selectively. A polyethylene glycol (PEG)‐conjugated Fe 2+ ‐containing hydroxide nanosheet is successfully constructed via a facile but efficient bottom‐up approach that concurrently realizes nanosheet synthesis and PEGylation. Importantly, the nanosheets are featured with high catalytic activity to disproportionate H2 O2 in tumors, and consequently generate abundant hydroxyl radicals at a high reaction rate under tumorous acidic condition; the highly toxic hydroxyl radicals, as a result, cause the death of tumor cells in vitro and suppress the tumor growth in vivo without the use of any supplementary toxic agent, only with the biocompatible nanocatalysts. Meanwhile, the desirable biodegradation and biocompatibility of the hydroxide nanosheet render a high degree of safety to the organism. Therefore, this work provides the first paradigm of biodegradable 2D nanocatalytic platform with concurrently high catalytic‐therapeutic performance and biosafety for efficient tumor‐specific treatment. Abstract : The new concept of nanocatalytic cancer therapy is demonstrated using a biodegradable 2D hydroxide nanosheet. The nanosheet is constructed via a novel bottom‐up method, and consists of polyethylene glycol and ferrous ions for enhanced aqueous dispersity, high catalytic capacity and tumor specificity, which are demonstrated by In vitro and in vivo evaluations.